Incidence of various reproductive disorders in swamp buffaloes of Assam - AHMED, K (The Indian Journal of Animal Reproduction, 2005)
Records of gynaeco-clinical examination of 203 swamp buffaloes maintained at Livestock Research Station, Mondira, Assam were studied. The study revealed anestrus to be a major reproductive problem followed by repeat breeding, rnetritis and pyornetra.